(untitled) (Revista de Ciências Agroveterinárias, 2019)
Canola (Brassica napus L. var. oleifera) is cultivated in the Southern Brazil as an alternative winter crop in the rotation system. No-tillage and hydromorphic soils favor the formation of aliphatic organic acids with short chain and low molecular weight, as acetic, butyric, and propionic acids. These acids may cause negative effects on the canola production. Thus, this study aimed to evaluate the response of five canola hybrid genotypes under the effect of acetic, butyric and propionic acids on the germination and initial phase of seedling growth. The results showed the characters evaluated respond differently to treatments applied within the same genotype. Therefore, the selection of a genotype with a resilient performance for the characters evaluated under stress is complex. Nevertheless, a sensitive profile response was observed in Hyola 433 genotype under different organic acids. Furthermore, acetic acid showed no negative impact on germination and initial growth of the genotypes.